الرقابة على الصفقات العمومية في المجالس المحلية - فـــــــلــيـــون, وداد; علية, مسعودة (جامعة الوادي university el-oued, 2022)
من خلال دراستنا لمختلف الآليات الرقابية الممارسة على الصفقات العمومية والمطبّقة على كل المراحل التي تمرّ بها الصفقة العمومية قبل دخولها حيّز التنفيذ، وقبل تنفيذها وبعده فنجدها على شكل رقابة إدارية تتمثّل في لجنة فتح الأظرفة وتقييم العروض على مستوى المصلحة المتعاقدة في شكل رقابة داخلية، ولتحقيق الهدف المرجو المتمثّل في حماية المال العام وجب فرض رقابة أخرى مكمّلة للأولى، تتمّ من طرف إحدى اللجان المختصة حسب المجال المفسوح لها للرقابة فيه والاختصاصات الممنوحة لها لأداء عملها بالإضافة إلى رقابة الوصاية الممارسة من قبل السلطة الوصية على المصلحة المتعاقدة. ولا تأخذ الصفقة صبغتها الشرعية إلا بعد إخضاعها لرقابة المراقب المالي والمحاسب العمومي والمراقب التقني في شكل رقابة مالية محاسبية، وسعيا من المشرّع الجزائري في تدعيم آليات الرقابة من الفساد ومكافحته والتي تعتبر أحد الآليات الرئيسية في نجاح السياسات الإصلاحية. Through our study of the various control mechanisms practiced on public deals and applied to all the stages that a public deal goes through before its entry into force, and before and after its implementation, we find it in the form of administrative oversight represented by the committee for opening envelopes and evaluating offers at the level of the contracting interest in the form of internal control, and to achieve The desired goal of protecting public money is required to impose another control complementary to the first, to be carried out by one of the competent committees according to the scope allowed for control in it and the competencies granted to it to perform its work in addition to the guardianship control exercised by the guardian authority over the contracting interest. The deal does not take its legal character until after it is subject to the control of the financial controller, the public accountant and the technical observer in the form of an accounting financial syndicate, and in an effort by the Algerian legislator to strengthen the control mechanisms against corruption and combating it, which is one of the main mechanisms in the success of reform policies.
مذكرة ماستر